Penerapan Pengendalian Internal Melalui Pengelolaan Persediaan Bahan Baku (Studi Kasus Pada CV. Cipta Gemilang Karya Mandiri) - Novita Wahyu; Endah Prawesti Ningrum (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2018)
Competition between companies is a problem faced by companies, making it increasingly difficult for the leadership to carry out direct supervision and coordination of all company activities. For this reason, it is necessary to apply internal control through the management of raw material supplies. With the aim of knowing how to apply internal control to the management of raw material inventory and how to manage raw material inventory. The method used is observation, interview, questionnaire and literature study. Data Analysis Methods that researchers do is Analyze the elements of the company's internal control system inventory, whether it is in accordance with existing theories and analyze the procedures for managing inventory of raw material inventory on CV. Cipta Gemilang Karya Mandiri. Application of internal control to the management of raw material supplies on the CV. Cipta Gemilang Karya Mandiri can be seen through the results of processing the questionnaire that the application of internal control plays a role of 80%, it is said that the application of internal control in the company is not optimal. Therefore, it is necessary to increase control over production costs, control the recording and proof of transactions, and control product customer demand.